Protein Concentrate from Shark - CHARI, S T; SREENIVASAN, A (Fishery Technology, 2017)
A simple method of leaching the minced muscle with water repeatedly followedby cooking, pressing, drying the cake and powdering has been describedfor the preparation of :fish protein concentrate (FPC) from shark without the useof solvents. The FPC thus prepared had a high protein content and wascompletely free of urea. It contained all the essential amino acids in abalanced proportion with a high lysine content and had a storage life upto12 months. This product can be used for the fortification of bread, biscuits and'chappathis' respectively at 10, 5 and 2% levels.